Hydraulic and ecological changes under drainage gate operations with coupled model SCHISM-CoSiNE in Saemangeum basin, Korea - Yoo, Hyung Ju; Jeong, Seokil; Kim, Dong Hyun; Lee, Seung Oh (Journal of Environmental Engineering and Landscape Management, 2021)
The drainage gates have been controlled for desalination under normal conditions and flood defense in  Saemangeum basin, Korea. Recently, it became an issue that the gates have been opened not to deteriorate water quality in the lake. It is, thus, necessary to precisely estimate the changes of water quality characteristics, especially DO, phosphate and nitrate, in the lake according to various gate operations. In this study, Semi-implicit Cross-scale Hydroscience Integrated System Model and Carbon, Silicate, Nitrogen Ecosystem model (SCHISM-CoSiNE) which is cable to simulate dynamic exchange such as gate operation conditions was utilized to obtain reliable and reasonable results including hydrodyanamic and environmental variables. For the verification, the measured data at 6 locations in Saemangeum basin was used to compare  incluidng temperatue and salintiy from 2016 and each relative error became small enough to show high accurary. Also, under various scenarios by changing the designated water surface elevation on flood seasons, this model has been applied to present the best designated water surface elevation in terms of both water quality and water supply in the Saemangeum basin. It becomes possbile to show reliable guidance for dynamic operations and environmental changes with this model as requested in near future.